Problems in the Implementation of Transformation Processes of Commercial Banks (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This document discusses Uzbekistan's digital transformation and privatization in banking. Phased actions, supported by presidential decrees, emphasize their role in shaping the digital economy. Challenges include a skilled workforce shortage, funding constraints, security issues, and resistance to change. Stages of digitization, capitalization impact, and a proposed privatization strategy are explored. The systematic, long-term approach is vital, and keywords encapsulate core themes. Uzbekistan positions itself for sustained growth and global competitiveness amid dynamic shifts in its banking sector.